Influence of handwriting skills during spelling in primary and lower secondary grades - Pontart, Virginie; Bidet-Ildei, Christel; Lambert, Eric; Morisset, Pauline; Flouret, Lisa; ALAMARGOT, Denis (Frontiers in Psychology, 2013)
We sought to identify, the impact of handwriting skills on the efficiency and temporal course of word spelling across Grades 2-9. Eighty-four students, drawn from primary and lower secondary schools, were asked to perform a dictation task to assess their word spelling. They also had to write out the letters of the alphabet, as well as their firstnames and surnames, from memory to assess their handwriting skills. Handwriting kinematics were recorded using a digitizing tablet and a computer running Eye and Pen software. Results revealed that graphomotor skills (as assessed by the name writing task) influenced the success and temporal course of spelling, but only in primary grades, whereas the influence of orthographic knowledge (as assessed by the alphabet task) could still be observed in the lower secondary grades, even if it ceased to influence the temporal course and only affected errors. We discuss what these findings tell us about changes in transcription processes over the course of child development.